Abstracts of the VIII congress of rheumatologists with international participation "Rheumatology 2021: multidisciplinary and interdisciplinary problems", dedicated to the 30th anniversary of the formation of the all-Russian public organization "association of rheumatologists of Russia - article Editorial (Научно-практическая ревматология)
.